The Clinical Value of Chemotherapy Combined With Capecitabine in Triple-Negative Breast Cancer—A Meta-Analysis - Zhang, Zilin; Ma, Kai; Li, Jing; Guan, Yeneng; Yang, Chaobo; Yan, Aqin; Zhu, Hongda (Frontiers in Pharmacology, 2021)
Purpose: Triple-negative breast cancer (TNBC) is the most dangerous subtype of breast cancer with high rates of metastasis and recurrence. The efficacy of capecitabine in chemotherapy for TNBC is still controversial. This study evaluated the efficacy and safety of capecitabine combining with standard, adjuvant or neoadjuvant chemotherapy for TNBC. Methods: We systematically searched clinical studies through PubMed, Cochrane library, Embase, Wanfang Database, China Academic Journals (CNKI), and American Society of Clinical Oncology's (ASCO) annual conference report. Studies were assessed for design and quality by the Cochrane risk of bias tool. A meta-analysis was performed using Review Manager to quantify the effect of capecitabine combined with standard, adjuvant or neoadjuvant chemotherapy on the disease-free survival (DFS) rate and overall survival (OS) rate of TNBC patients. Furthermore, safety analysis was performed to evaluate the adverse events. Results: Twelve randomized controlled clinical trials involving totally 4854 TNBC patients were included, of which 2214 patients received chemotherapy as control group, and 2278 patients received capecitabine combining with chemotherapy. The results indicated that capecitabine could significantly improve the DFS [hazard ratio (HR) 0.80, 95% confidence interval (CI) 0.71-0.90, P=0.0003] and OS (HR 0.83, 95% CI 0.74-0.93, P=0.001). In subgroup analysis, the combination of capecitabine and cyclophosphamide exhibited a significant benefit in all outcomes (DFS HR 0.75, 95%CI 0.63-0.90, P=0.002; OS HR 0.65, 95%CI 0.52-0.80, P＜0.0001). Additionally, defferent dose of capecitabine subgroup showed same significant effect on the results. Safety analysis showed that the addition of capecitabine was associated with a much higher risk of hand-foot syndrome, diarrhea and mucositis or stomatitis. Conclusion: The results showed that adjuvant capecitabine could bring significant benefits on DFS and OS to unselected TNBC patients, the combination of capecitabine and cyclophosphamide could improve the survival rate of patients, although the addition of capecitabine could bring significant side effects such as HFS and diarrhea.